Role of MicroRNA in Proliferation Phase of Wound Healing - Soliman, Amro M.; Das, Srijit; Abd Ghafar, Norzana; Teoh, Seong Lin (Frontiers in Genetics, 2018)
Wound healing is a complex biological process that is generally composed of four phases: hemostasis, inflammation, proliferation and remodelling. The proliferation phase is crucial for effective healing compared to other phases. Many critical events occur during this phase, i.e. migration of fibroblasts, re-epithelialization, angiogenesis and wound contraction. Chronic wounds are common and are considered a major public health problem. Therefore, there is the increasing need to discover new therapeutic strategies. MicroRNA (miRNA) research in the field of wound healing is in its early phase, but the knowledge of the recent discoveries is essential for developing effective therapies for the treatment of chronic wounds. In this review, we focused on recently discovered miRNAs which are involved in the proliferation phase of wound healing in the past few years and their role in wound healing.